Odpowiedzi

2009-10-11T13:15:01+02:00
X2+12x+36=(x+6)2
x2+10x+25=(x+5)2
36x2+12x+1=(6x+1)2
x2+4xy+4y2=(x+2y)2
x2-8x+16=(x-4)2
9x2-6x+1=(3x-1)2
9x2-12x+4=(3x-2)2
x2-6xy+9y2=(x-3y)2
2 4 2
2009-10-11T13:15:53+02:00
X2+12x+36=(x+6)²
x2+10x+25=(x+5)²
36x2+12x+1=(6x+1)²
x2+4xy+4y2=(x+2y)²
x2-8x+16=(x-4)²
9x2-6x+1=(3x-1)²
9x2-12x+4=(3x-2)²
x2-6xy+9y2=(x-3y)²
2 5 2
2009-10-11T13:27:43+02:00
X2+12x+36=(x+6)²
sprawdzenie: (x+6)²=x²+(2*x*6)+6²=x²+12x+36 zgadza się

x2+10x+25=(x+5)²
sprawdzenie: (x+5)²=x²+(2*5*x)+5²=x²+10x+25 zgadza się

36x2+12x+1=(6x+1)²
sprawdzenie: (6x+1)²=(6x)²+(2*6x*1)+1²=36x²+12x+1 zgadza się

x2+4xy+4y2=(x+2y)²
sprawdzenie: (x+2y)²=x²+(2*x*2y)+(2y)²=x²+4xy+4y² zgadza się

x2-8x+16=(x-4)²
sprawdzenie: (x-4)²=x²-(2*4*x)+(-4)²=x²-8x+16 zgadza się

9x2-6x+1=(3x-1)²
sprawdzenie: (3x-1)²=(3x)²-(2*1*3x)+(-1)²=9x²-6x+1 zgadza się

9x2-12x+4=(3x-2)²
sprawdzenie: (3x-2)²=(3x)²-(2*3x*2)+(-2)²=9x²-12x+4 zgadza się

x2-6xy+9y2= (x-3y)²
sprawdzenie: (x-3y)²=x²-(2*3y*x)+(-3y)²=x²-6xy+9y²
6 4 6